2011
DOI: 10.1002/ejlt.201100100
|View full text |Cite
|
Sign up to set email alerts
|

Phytosterols in human nutrition: Type, formulation, delivery, and physiological function

Abstract: Phytosterols are a family of compounds similar to cholesterol which have been shown to lower cholesterol levels when supplemented in the diet. A daily dose of 2-3 g of phytosterols has been shown to reduce LDL-cholesterol levels by 5-15%. Phytosterol supplementation can be undertaken using phytosterol enriched functional foods or nutraceutical preparations. The type of phytosterol supplemented, such as plant sterol or saturated plant stanol appear to be equally effective in lowering cholesterol levels. Phytost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
45
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(46 citation statements)
references
References 60 publications
0
45
0
1
Order By: Relevance
“…Phytosterols (PS) are plant‐derived natural steroid compounds and mainly originate from vegetable oils, plant seeds and legume products . With a similar structure to cholesterol, PS have been shown to reduce cholesterol absorption via competitive inhibition . Medical research has revealed the beneficial effects of PS on immune regulation and anti‐inflammatory activity in vitro .…”
Section: Introductionmentioning
confidence: 99%
“…Phytosterols (PS) are plant‐derived natural steroid compounds and mainly originate from vegetable oils, plant seeds and legume products . With a similar structure to cholesterol, PS have been shown to reduce cholesterol absorption via competitive inhibition . Medical research has revealed the beneficial effects of PS on immune regulation and anti‐inflammatory activity in vitro .…”
Section: Introductionmentioning
confidence: 99%
“…Their importance in the characterization and detection of oil mixtures are of great interest (Aparicio and Aparicio-Ruiz, 2000;Janssen et al, 2009). Also, the nutritional value of edible oils depends on the content and composition of biological active compounds from this fraction such as phytosterols which prevent the intestinal absorption of cholesterol in humans, resulting in a lowering of serum cholesterol (Mackay and Jones, 2011) or tocopherols, vitamin E compounds only synthesized by plants, which are well recognized for their effective inhibition of lipid oxidation in foods and biological systems (KamalEldin and Appleqvist, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…They are structurally similar to cholesterol with some differences in the D-ring side chain (1)(2)(3). The term phytosterols is widely used to describe both plant sterols, which have a double bond at position 5 of the sterol ring, and plant stanols in which the double bond is saturated (4,5) (Figure 1). Phytosterols are extracted from vegetable oils such as corn oil, rapeseed oil, soybean oil, sunflower oil, olive oil and tall oil either in free forms or as fatty acid esters (6).…”
Section: Introductionmentioning
confidence: 99%